CANON ENGR. PROF. NKEMAKONAM NWOLISA OSADEBE, 1955 – 2015 (Nigerian Journal of Technology, 2015)
The news of the death of Canon Engr. Prof. Nkemakonam Nwolisa Osadebe on Friday 23rd October, 2015 was a great shock to us. It was as if the activities in the Faculty of Engineering, University of Nigeria, Nsukka was brought to a standstill by the passing away of such an academic luminary known nationally and internationally.